Ergosterol Alleviates Kidney Injury in Streptozotocin-Induced Diabetic Mice. (17th November 2015) - Ang, Li; Yuguang, Liu; Liying, Wang; Shuying, Zhang; Liting, Xu; Shumin, Wang
Abstract : Ergosterol (ERG) has been widely used in the development of novel drugs due to its unique physiological function. However, little is known about the protective effects of ERG on diabetes. Hence, the current study was designed to evaluate the positive role of ergosterol on streptozotocin- (STZ-) induced diabetes in mice. Oral glucose tolerance test (OGTT) was carried out to assess blood glucose level. Biochemical parameters such as uric acid, creatinine, serum insulin, triglycerides (TG), and total cholesterol (TC) were also measured. Pathological condition of kidney was examined by hematoxylin-eosin (H&E) staining. The expressions of PI3K, p-PI3K, Akt, p-Akt, NF- κ Bp65, p-NF- κ Bp65, I κ B α, and p-I κ B α were analyzed by western blot. ERG significantly reduced the concentrations of blood glucose, uric acid, creatinine, TG, and TC. Serum insulin was elevated with ERG treatment. In addition, renal pathologic changes of diabetes mice were also alleviated by ERG. Obtained data revealed that ERG restored the levels of PI3K/Akt/NF- κ B signaling-related proteins in comparison with diabetes mice. Above all, it could be assumed that ERG might play a positive role in regulating STZ-induced diabetes through suppressing PI3K/Akt/NF- κ B pathway.